Emotional intelligence and quality of life - Šverko Vižintin, Dina (Array, 2011)
The present study examined the relationship between emotional intelligence and quality of life in a sample of 324 volunteers (163 males and 161 females) who were gathered by predetermined quotas. In order to determine the incremental predictive validity of emotional intelligence for the quality of life criteria, the five-factor personality traits and dispositional affect (positive and negative affect) already known to predict quality of life were also assessed. Both, a self-report and an ability-based measure of emotional intelligence were used. The overall quality of life and more specific, health-related quality of life were assessed each by a single-item measure. Emotional intelligence and personality dispositions showed significant correlations in the expected direction with quality of life measures. Further, the results of hierarchical multiple regression analyses revealed that the employed system of predictor variables explained 26% of the overall quality of life variance and 19% of the variance of health-related quality of life. Within the set of predictors employed, the five-factor personality traits showed the largest predictive power. After controlling for five personality dimensions and dispositional affect, emotional intelligence measures accounted for additional variance in health-related quality of life but not in the overall quality of life. More precisely, the obtained results suggest that of the two types of emotional intelligence measures used just the self-reported emotional intelligence shows independent contribution to the health-related quality of life variance.